From The Iron Curtain to Franco's Spain: Right-Wing Central Europeans in Exile. (2nd January 2018) - Eiroa, Matilde
ABSTRACT: After the Second World War, anti-communists of different backgrounds from Central and Eastern European countries decided to settle in Franco's Spain, where they sought safety and a place to live during the Cold War. This article will provide an overview of their political profiles and assess the reasons these exiles chose Spain, a country excluded from the United Nations until 1955 and led by Francisco Franco. The article also shows how they settled in the dictatorship linked to the Nazis and Italian Fascists, and the ways in which they continued their struggles against Communism with public and private resources.